Exchange Rate Misalignment and Economic Growth in Pakistan: The Role of Financial Development (The Pakistan Development Review, 2020)
This study endeavours to examine empirically how real exchange rate (RER) misalignment affects economic growth in Pakistan. In this regard, we have not only estimated the direct impact but also the indirect impact of misalignment on economic growth by using the financial development channel. We have used time series data ranging from 1980 to 2016 to carry out the empirical analysis. After testing the time series properties of the selected variables, we computed long run equilibrium RER later used to calculate RER misalignment. Finally, we estimated the impact of misalignment on per capita economic growth, both direct and indirect. Our results reveal an adverse impact of RER misalignment on economic growth. However, we report that financial development helps in minimising the adverse impact of RER misalignment, though not fully eliminating it. Based on the empirical findings, the study suggests that exchange rate policies need to be managed more cautiously. Moreover, the financial sector development needs to be strengthened which may help in fully alleviating the adverse impact of RER misalignment on economic growth. JEL Classification: F31, GOO, O47 Keywords: Real Exchange Rate Misalignment, Financial Development, Economic Growth, FMOLS